استهلاك المخدارت والمؤثرات العقلية وعلاقتها بالجريمة لدى المراهق المتمدرس - الزعيم, حراش (جامعة الوادي university of Eloued, 2022)
الملخص: تعد مشكلة تعاطي المخدرات من المشكلات التي تهدد المجتمعات حث انها تستهدف المجتمع بجمع فئاته العمرية والاجتماعية. وتكمن الخطورة العظمى والاشد ضررا لهذه المشكلة في انها تستهدف فئة الشباب بالذات.مما ينعكس سلبا عللا كافة النواحي النفسية والاجتماعية ويختلف اثار على مستوى المشاعر والانفعالات ولكن ايضا على مستوى السلوك الذي يؤدي الى اضطرابات سلوكية من بينها السلوك العدواني الذي حاولنا دراسته من خلال المنهج الاكلينيكي وكذا استعمال المقابلة النصف موجهة بهدف البحث واستبيان السلوك العدواني ل بيري وباص واضهرت النتائج ان لمتعاطي المخدرات وخاصة فئة المراهقين اثر في ظهور العدوانية لدى المراهق وهذه الاخيرة التي لاتاخذ شكلا واحدا وانما تتعدد اشكالها فقد تظهر في شكل عدوانية موجهة نحو الذات او عدوانية موجهة نحو الغير وخاصة فئة المراهقين. الكلمات المفتاحية: المخدرات - الجريمة - المراهق Abstract : The problem of drug abuse is one of the problems that threaten societies, as it targets society by all its age and social groups. The greatest danger and most damaging of this problem lies in that it targets the youth category in particular. This reflects negatively on all psychological and social aspects and has different effects on the level of feelings and emotions, but also on the level of behavior that leads to behavioral disorders, including the aggressive behavior that we tried to study through the clinical approach, as well as The use of the semi-directed interview in order to research and questionnaire the aggressive behavior of Perry and Bus. The results showed that drug users, especially the adolescent group, had an impact on the appearance of aggression among adolescents, and the latter, which does not take one form, but rather takes many forms, it may appear in the form of aggressiveness directed towards oneself or aggressiveness directed towards others, especially a group teenagers. Keywords: drugs, crime, adolescents
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: الجريمة، المخدرات، المراهقة; Crime, drugs, adolescence; Criminalité, drogue, adolescence